Health Education On Prevention Of Dental Caries In Children - Holipa, Sinta; Emirsadiq , Denny; Lestari , Rapita; Anntoni , Sendya Putri; Gustina , Zelta; Habibi , Julius (Jurnal Pengabdian Mandiri, 2024)
One of the most common dental health problems Indonesian people suffer is dental caries. The highest prevalence of dental caries is in children. The incidence of dental caries in children is influenced by parental behavior in the habit of giving sweet, sticky food and drinking milk, the habit of maintaining children's dental hygiene and the habit of examining the child's teeth and mouth. In children who experience dental caries, they will experience pain in the mouth, difficulty chewing, disturbed eating patterns, difficulty sleeping, difficulty concentrating which can interfere with children's learning and social activities. Knowledge is a very important domain for shaping behavior. The results showed that there was a relationship between mother's knowledge about oral health and the incidence of dental caries in children. The purpose of community service is for parents to understand about preventing dental caries in children. The Method in community service are lectures, discussions, and questions and answers. The target in community service are 9 parents. The results of community service are increasing parental knowledge about preventing dental caries in children.